Konflik Kepentingan dalam Hak Kebendaan di atas Benda Milik Orang Lain: Antara Perlindungan Pemilik dan Hak Preferensi Kreditor - Nur Najma, Siti Najla; Az-Zahra, Fatimah; Febrian, Matthew; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the conflict of interest arising from the exercise of property rights over another person’s assets within Indonesia’s civil law system. Property law not only protects ownership rights but also serves as a legal instrument to guarantee creditors and third parties in the modern economy. The core issue emerges when absolute ownership rights conflict with limited real rights that grant preferential status to creditors. Using a normative juridical method through analysis of legislation, legal doctrines, and court decisions such as Supreme Court Rulings No. 2911 K/Pdt/2019 and No. 1248 K/Pdt/2007, this study finds that the existence of real rights has transformed ownership from an absolute concept into a relative or functional one. While owners retain their rights, these rights are limited by the existence of real rights to ensure legal certainty for creditors. The study concludes that harmonization is needed between ownership protection and creditor certainty through clearer regulations, strict procedural enforcement, and increased legal awareness to achieve a balance between legal certainty and substantive justice in property law practice.